PENINGKATAN HASIL BELAJAR MATERI HIDROKARBON MELALUI PENGGUNAAN SOFTWARE CHEMDRAW DI SMKN 1 BP BANGSA RAJA - DIANA NOVITASARI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Technological development in education requires an educator to be creative and innovative in creating an interactive learning atmosphere on hydrocarbon material which is classified as abstract and is considered difficult for students to understand. Technology-based learning that has been developed in this research is to use ChemDraw software as an alternative to interactive learning to replace conventional methods. The research method used is using the pretest and posttest methods with the aim of seeing the effect of using ChemDraw software on increasing student learning outcomes on hydrocarbon material. The test data were analyzed using the N-Gain test, t test and effect size. Based on the results of the calculation of the pretest and posttest scores, there was an increase in the average score of class X students at SMK N 1 BP. BR from 64.9 to 89.15, while the average value of N-Gain is 0.69 or 69%. This shows that the application of the ChemDraw software learning media is proven to be effective in improving the learning outcomes of students in the medium category. In the t-test obtained -1.68 < tcount < 1.68 and the occurrence of rejecting Ho and accepting H1 which shows that there is a difference in the average score before and after using the software. While the results of the analysis of the effect size of 0.87 which is quite strong. This shows that there is a strong influence and good effectiveness in the use of ChemDraw software on hydrocarbon materials to improve student learning outcomes. ABSTRAKPerkembangan teknologi dalam dunia pendidikan menuntut seorang pendidik menjadi kreatif dan inovatif dalam menciptakan suasana belajar interaktif pada materi hidrokarbon yang tergolong abstak dan dianggap sulit dipahami oleh siswa. Pembelajaran berbasis teknologi yang telah dikembangkan pada penelitian ini ialah dengan memanfaatkan software ChemDraw sebagai alternatif pembelajaran interaktif pengganti metode konvesional. Metode penelitian yang digunakan ialah menggunakan metode pretest dan postest dengan tujuan melihat penggaruh penggunaan software ChemDraw terhadap peningkatan hasil belajar siswa pada materi hidrokarbon. Data hasil tes dianalisis menggunakan uji N-Gain, uji t dan effect size. Berdasarkan hasil perhitungan nilai pretest dan posttest, terjadinya peningkatan nilai rata-rata siswa kelas X SMK N 1 BP. BR dari 64,9 menjadi 89,15, sedangkan nilai rata-rata N-Gain sebesar 0,69 atau 69%. Hal ini menunjukkan bahwa penerapan media pembelajaran software ChemDraw terbukti efektif dalam meningkatkan hasil belajar peserta didik dengan kategori sedang. Pada uji t diperoleh -1,68 < thitung < 1,68 dan terjadinya tolak Ho dan terima H1 yang menunjukkan terdapat perbedaan rata-rata skor sebelum dan sesudah penggunakan software. Sedangkan hasil analisis effect size sebesar 0,87 yakni tergolong kuat. Hal ini menunjukkan adanya pengaruh yang kuat dan efektifitas yang baik dalam penggunaan software ChemDraw pada materi hidrokarbon terhadap peningkatan hasil belajar siswa.